Kemiskinan dan Struktur Sosial di Maluku Dalam Perspektif Social Capital - Fridolin R Kwalomine (Program Pascasarjana UKIM, 2021)
This article aims to analyze the poverty problems and social structure in Maluku from a social capital perspective. Poverty is a human problem that hinders prosperity and civilization. The discourse of poverty in Indonesia to Maluku remains a crucial discourse to discuss and find a solution. Poverty has become a chronic problem because it is related to gaps and unemployment. In a proper sense, poverty is understood as a state of lack of money and goods to ensure survival. In Maluku, the latest data on poverty was recorded by BPS (center for statistic data) as of 2020 from September 2020, BPS recorded the number of poor people in Maluku amounting to 322.40 thousand people, or an increase of 4.2 thousand people when compared to March 2020, which was 318.18 thousand souls. Using a qualitative descriptive approach, this article offers a mapping of problems and approaches to social capital to address the acute problem of poverty in Maluku.